MANAJEMEN SUMBER DAYA MANUSIA DI TK IT NUR AL IZHAR KEBONSARI (STUDI KASUS PENGEMBANGAN GURU) - Anwar, Rosyida Nurul; Alfina, Alisa (Universitas Islam Malang, 2019)
Human resource management is oriented to optimizing a working system in an organization. Kindergarten teacher development management is needed to meet the qualifications so that all teachers are able to have competence in the field of early childhood education so as to improve the quality of educational institutions, Early childhood is a golden age or golden age, so in learning kindergarten teachers do not only act as a conveyer of information to students However, teachers are required to have the ability and understand the uniqueness of each student in order to help them in various difficulties in developing creativity and learning. This research uses a qualitative approach to the type of case study. Data collection techniques carried out by observation, interviews, and documentation. Analysis of Miles and Huberman's model, namely data collection, data reduction, data presentation, and concluding become the data analysis techniques in this study. The research findings show that teacher development at TK IT Nur Al Izhar is done by coaching, counseling, mentoring, motivating, and empowering through; 1) professional training, 2) collective activities of teachers such as Clusters, IGTKI, KKG, and PGRI, 3) participation in scientific forums in the form of technical guidance, workshops, seminars, 4) mentoring the learning process.